Genes VIII - Lewin, Benjamin (Pearson Prentice Hall, 2004)
For courses in molecular biology, molecular genetics, and gene regulation, 'Genes VIII' begins with the sequence of the human and other genomes and starts with complete coverage of advances in genomics. The coverage of genomics is then integrated throughout the text.